A fellowship of bakers & magic - Penner, Jenetta (Penner, Jenetta, Adenashire, 2025)
"A human, a dwarf and an elf walk into a bake-off... In the heart of Adenashire, where elfish enchantments and dwarven delights rule, human confectioner Arleta Starstone works twice as hard at perfecting her unique blend of baking and apothecary herbs. So when an orc neighbor secretly enters her creations into the prestigious Elven Baking Battle, Arleta faces a dilemma. Being magicless, her participation in the competition could draw more scowls than smiles. And if Arleta wants to prove her talent and establish her culinary reputation, this human will need more than just her pastry craft to sweeten the odds. While competing, she'll set off on a journey of mouthwatering pastries, self-discovery, heartwarming friendships and romance, while questioning whether winning the Baking Battle is the true prize." --